Pancreatic metastasis from non-small-cell lung cancer diagnosed using endoscopic ultrasound-guided fine needle aspiration biopsy: A case report - Kurihara, Nobuyasu; Saito, Hajime; Nanjo, Hiroshi; Konno, Hayato; Minamiya, Yoshihiro (Turkish Journal of Gastroenterology, 2017)
Abstract A 56-year-old man presented with a chest computed tomography (CT) finding of a right upper lobe nodule, which was diagnosed using brush cytology as adenocarcinoma stage IB (cT2aN0M0). Repeat CT scan for preoperative evaluation revealed a small, slightly hypodense spot in the pancreatic body, which was diagnosed as pancreatic metastasis from lung cancer using endoscopic ultrasound-guided fine needle aspiration biopsy (EUS-FNAB). Because of the presence of distant metastasis, surgical resection was deferred and chemotherapy was chosen instead. Pancreatic metastasis from non-small-cell lung cancer (NSCLC) is rare and might present with few symptoms when the tumor is small. EUS-FNAB is a useful modality for detecting and providing accurate histological diagnosis of pancreatic tumors. Although pancreatic metastasis from NSCLC is rare, appearance of a new lesion in the pancreas should immediately warrant EUS-FNAB. Cite this article as: Kurihara N, Saito H, Nanjo H, Konno H, Minamiya Y. Pancreatic metastasis from non-small-cell lung cancer diagnosed using endoscopic ultrasound-guided fine needle aspiration biopsy: a case report. Turk J Gastroenterol 2017; 28: 502-4.